2002
DOI: 10.1074/jbc.m112157200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Receptor Protein-tyrosine Phosphatase, PTPμ, Restores E-cadherin-dependent Adhesion in Human Prostate Carcinoma Cells

Abstract: Normal prostate expresses the receptor protein-tyrosine phosphatase, PTP, whereas LNCaP prostate carcinoma cells do not. PTP has been shown previously to interact with the E-cadherin complex. LNCaP cells express normal levels of E-cadherin and catenins but do not mediate either PTP-or E-cadherin-dependent adhesion. Re-expression of PTP restored cell adhesion to PTP and to E-cadherin. A mutant form of PTP that is catalytically inactive was re-expressed, and it also restored adhesion to PTP and to E-cadherin. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 30 publications
4
65
1
1
Order By: Relevance
“…The increased expression of PTPRM in normal cell and low-grade astrocytomas compared to high grade glioblastomas, along with the results of in vivo experiments, also confirmed that loss of this protein promotes tumor cell migration and propagation (17). The lack of expression of PTPRM in prostate cancer cells connected with the lack of PTPRM-mediated adhesion also suggests a role of PTPRM as a tumor suppressor gene (16). AlthoughtAlthough these autorsauthors have not mentioned about PTPs in theirtop "top ranking lists" of genes with aberrant methylation, the available raw data shows differences in PTPs methylation accordingas compared to healthy tissue (19,20).…”
Section: Ptprm (Ptpr-mu) Is a Member Of The Ig Superfamily Of Adhesiosupporting
confidence: 59%
See 1 more Smart Citation
“…The increased expression of PTPRM in normal cell and low-grade astrocytomas compared to high grade glioblastomas, along with the results of in vivo experiments, also confirmed that loss of this protein promotes tumor cell migration and propagation (17). The lack of expression of PTPRM in prostate cancer cells connected with the lack of PTPRM-mediated adhesion also suggests a role of PTPRM as a tumor suppressor gene (16). AlthoughtAlthough these autorsauthors have not mentioned about PTPs in theirtop "top ranking lists" of genes with aberrant methylation, the available raw data shows differences in PTPs methylation accordingas compared to healthy tissue (19,20).…”
Section: Ptprm (Ptpr-mu) Is a Member Of The Ig Superfamily Of Adhesiosupporting
confidence: 59%
“…shown to be expressed in neurons, glia, epithelia and prostate (16,17,18). PTPRM plays a crucial role in EGFR signaling -reduced expression of PTPRM increases the EGFR specific phosphorylation of tyrosine residue, thus causing phospholipase C-gamma (PLC)γ1 activation and cell migration (18).…”
Section: Ptprm (Ptpr-mu) Is a Member Of The Ig Superfamily Of Adhesiomentioning
confidence: 99%
“…Perhaps Rack1 inhibits other tyrosine kinases from phosphorylating the E-cadherin/catenin complex and/or recruits tyrosine phosphatases to dephosphorylate the complex. Thus, we examined Rack1's influence on protein tyrosine phosphatase m (PTPm), a tyrosine phosphatase that is known to associate with the E-cadherin/ catenin complex (Brady-Kalnay et al, 1995 and with Rack1 (Mourton et al, 2001;Hellberg et al, 2002;Chattopadhyay et al, 2003). We did not observe changes in PTPm expression or in the association of PTPm with E-cadherin in cells overexpressing Rack1 (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…However, it is possible that other RACK1-interacting proteins are also involved in regulating Akt activity. For example the regulatory phosphatase PTP interacts with RACK1 and was found to be active in regulating focal adhesions via PKC␦ (47,49). It will be necessary to do a complete analysis of RACK1-associated proteins in response to IGF-1 or insulin stimulation of cells to get a comprehensive picture of how RACK1 regulates signaling from these receptors.…”
Section: Igf-1r Kinase Activity Is Enhanced In Mcf-7 Cellsmentioning
confidence: 99%